PENGARUH PENERAPAN PENDEKATAN RESOURCE BASED LEARNING TERHADAP HASIL BELAJAR SEJARAH - Melisa Rahayu; Iskandar Syah; Yustina Sri Ekwandari (PESAGI (Jurnal Pendidikan dan Penelitian Sejarah), 2014)
Problem identification of the research is whether there are any effects of resource based learning approach to the student cognitive study result in term of Historical subject to the students of 10th grade of SMA Tri Sukses Natar. The purpose of the research is to find out the effects of resource based learning approach to the student cognitive study result in term of Historical subject to the students of 10th grade of SMA Tri Sukses Natar. Research design is using pre-test and post-test control group design. Population of research involved all students of 10th grade of SMA Tri Sukses Natar academic year 2013/2014 which are 206 students. The sample has been taken by using random sampling technique. The conclusion of the research, there is an effect of resource based learning approach to the student cognitive study result in term of Historical subject of 10th grade of SMA Tri Sukses Natar.Rumusan masalah penelitian adalah apakah ada pengaruh penerapan pendekatan Resource Based Learning terhadap hasil belajar kognitif siswa pada Mata Pelajaran Sejarah kelas X SMA Tri Sukses Natar. Tujuan penelitian ini adalah mengetahui pengaruh penerapan pendekatan Resource Based Learning terhadap hasil belajar kognitif siswa pada Mata Pelajaran Sejarah kelas X SMA Tri Sukses Natar. Desain penelitian adalah pretest-postest control group design. Populasi penelitian adalah seluruh siswa kelas X SMA Tri Sukses Natar tahun ajaran 2013/2014 yang berjumlah 206 orang. Sampel diambil dengan menggunakan teknik random sampling. Berdasarkan penelitian disimpulkan bahwa ada pengaruh penerapan pendekatan Resource Based Learning terhadap hasil belajar kognitif siswa pada Mata Pelajaran Sejarah kelas X SMA Tri Sukses Natar.Kata kunci : hasil belajar, pembelajaran sejarah, resource based learning